Current understanding of T cell immunity against SARS-CoV-2 - Xiuyuan Lu; Sho Yamasaki (BMC, 2022)
Abstract As an important part of adaptive immunity, T cells are indispensable in the defense against pathogens including viruses. SARS-CoV-2 is a new human coronavirus that occurred at the end of 2019 and has caused the COVID-19 pandemic. Nevertheless, most of the infected patients recovered without any antiviral therapies, suggesting an effective immunity developed in the bodies. T cell immunity responds upon SARS-CoV-2 infection or vaccination and plays crucial roles in eliminating the viruses and generating T cell memory. Specifically, a subpopulation of CD4+ T cells could support the production of anti-SARS-CoV-2 antibodies, and cytotoxic CD8+ T cells are also protective against the infection. SARS-CoV-2-recognizing T cells could be detected in SARS-CoV-2-unexposed donors, but the role of these cross-reactive T cells is still in debate. T cell responses could be diverse across individuals, mainly due to the polymorphism of HLAs. Thus, compared to antibodies, T cell responses are generally less affected by the mutations of SARS-CoV-2 variants. Up to now, a huge number of studies on SARS-CoV-2-responsive T cells have been published. In this review, we introduced some major findings addressing the questions in the main aspects about T cell responses elicited by SARS-CoV-2, to summarize the current understanding of COVID-19.